Creative student worksheets via project-based learning on electrolyte and non-electrolyte solutions - Molani Paulina Hasibuan Hasibuan; Santi; Ratih Permana Sari; Ricky Andi Syahputra; Florentina Maria Panda; Titin Rahmayanti Rambe (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2025)
Creative thinking skills are essential for 21st-century learning, yet Indonesian students' creativity levels remain below international standards, particularly in chemistry education where traditional approaches dominate. This study developed student worksheets (LKPD) that integrate creative values within a Project-Based Learning (PjBL) framework for electrolyte and non-electrolyte solutions topic. Using the ADDIE development model, data were collected from chemistry teachers, education lecturers, and students through validation questionnaires and analyzed descriptively. Results demonstrated high teacher demand for creative-value LKPD, with expert validation confirming the product as feasible for classroom implementation. Teacher responses indicated the worksheets were highly practical, while students found them very attractive and engaging. The developed LKPD successfully met validity, practicality, and attractiveness criteria. This research contributes theoretically by demonstrating the effectiveness of integrating creative values with PjBL in chemistry education, while practically providing educators with an innovative instructional tool that enhances student creativity, engagement, and active learning. The findings support the potential of creative-value worksheets to transform traditional chemistry instruction and foster 21st-century skills development.